The Playing Techniques of Balo-Balo in Kampung Tirang, Tegal Barat Subdistrict, Tegal City - Ferdianto Zain; Sunarto Sunarto (Universitas Muhammadiyah Enrekang, 2025)
This study aims to describe the playing techniques of the traditional performing art Balo-Balo, which has developed in Kampung Tirang, Tegal Barat District, Tegal City, as well as to explore the educational values embedded within it. The research adopts an ethnomusicological approach based on Alan P. Merriam’s theory, which views music as an integrated system comprising sound, musical behavior, and cultural concepts. The study employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation involving local performers and community members. The findings reveal that Balo-Balo playing techniques involve role specialization for each musical instrument, such as Terbang Induk, Kempling, Kempyang, and Konteng, all of which are played collectively without the use of standardized musical notation. The learning process is carried out through oral tradition and direct practice, reflecting a cultural transmission model rooted in kinesthetic and non-written forms. Social values such as mutual cooperation, discipline, collaboration, and the preservation of local culture are reflected in the performance practice. These findings indicate that Balo-Balo’s playing techniques not only hold musical significance but also possess strong potential as a medium for culturally rooted arts education, character development, and the reinforcement of cultural identity within both formal and non-formal educational settings.